Accident Reconstruction and Assessment of Cyclist's Injuries Sustained in Car-to-bicycle Collision. (2017) - Raslavičius, Laurencas; Bazaras, Liudas; Keršys, Robertas
Abstract: Cyclists have the largest risk of severe injury when colliding with a motor vehicle. The difference in weight (mass) is huge and the collision energy is mainly absorbed by the lighter 'object'. A cyclist simulation study captured kinematics and injuries to head, torso, pelvis and legs for one human body size, bicycle type and car model. We analysed the number of parameters, such as pelvic acceleration, Neck tension force, Neck shear force, Head injury criterion, forces acting on left and right tibia for the specific case of car-to-bicycle collision – bicyclist ride-out-residential driveway. Simulation showed that the windscreen is a frequent head and torso impact location. We found the gap in technical literature on injuries mitigated as well as on the documented effect of legislation, which until now has not been as impressive in different countries as hoped. Bridging the implementation gap between science and policy actions for the safer cycling would be a reasonable step towards decreasing the number of injured cyclists and road traffic death rates.